Inflammatory Cytokines Alter Mesenchymal Stem Cell Mechanosensing and Adhesion on Stiffened Infarct Heart Tissue After Myocardial Infarction - Zhu, Dan; Wu, Peng; Xiao, Changchen; Hu, Wei; Zhang, Tongtong; Hu, Xinyang; Chen, Wei; Wang, Jian’an (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cells (MSCs) transplantation has demonstrated its potential in repairing infarct heart tissue and recovering heart function after myocardial infarction (MI). However, its therapeutic effect is still limited due to poor MSC engraftment at the injury site whose tissue stiffness and local inflammation both dynamically and rapidly changes after MI. Whether and how inflammatory cytokines could couple with stiffness change to affect MSC engraftment in the infarct zone still remain unclear. In this study, we characterized dynamical stiffness changes of and inflammatory cytokine expression in the infarct region of rat heart within a month after MI. We found that the tissue stiffness of the heart tissue gradually increased and peaked in twenty-one days after MI along with the rapid upregulation of TNF-α, IL-6 and IL1-β in first three days followed by a sharp declination. We further in-vitro demonstrated that immobilized inflammatory cytokine IL-6 performed better than soluble form in enhancing MSC adhesion to stiffened substrate through IL-6/SHP-2/integrin signaling axis. We also confirmed such mechano-immune coupling of tissue stiffness and inflammatory cytokines in modulating MSC engraftment in the rat heart after MI in vivo. Our study provides new mechanistic insights of mechanical-inflammation coupling to improve MSC mechano-sensing and adhesion, potentially benefiting MSC engraftment and its clinical therapy for MI.